RESERVOIR SEDIMENTATION STUDIES USING SATELLITE REMOTE SENSING TECHNIQUE AND MATHEMATICAL MODELING - MR. R. M. MANE; PROF. P.A. HANGERGEKAR (International Journal of Innovations in Engineering Research and Technology, 2021)
Sedimentation in the reservoir gradually reduces its storage capacity. By keeping a check on the sedimentation and by providing control measures for the same, the reservoir life can be maintained. Ujjani dam was constructed for irrigation, water supply and power generation schemes. It lies in Solapur district which is a drought prone area. This makes Ujjani a socially and economically significant project for the state. In the present study, reservoir sedimentation for Ujjani reservoir is assessed for monitoring purpose. Two techniques namely Satellite Remote Sensing Technique (SRST) and mathematical modeling using HEC RAS, were used in the study for estimating sedimentation.